2022
DOI: 10.1159/000522538
|View full text |Cite
|
Sign up to set email alerts
|

Quality Issues in Diagnostic Immunohistochemistry in Breast Pathology

Abstract: Immunohistochemistry techniques have been incorporated into surgical pathology for nearly a half-century and have since become intimately intertwined with its practice. In the realm of breast pathology, immunohistochemistry serves several purposes, including providing crucial prognostic and predictive data. Among its other applications, assessment of stromal invasion and establishment of mammary origin are crucial from a diagnostic standpoint. In these regards, sole reliance on immunohistochemistry may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…12 At the other end of the spectrum, apocrine ductal carcinoma in situ with high nuclear grade shows marked nuclear pleomorphism and prominent nucleoli. 12 Despite that tumor cells with apocrine differentiation have large nuclei and prominent nucleoli and are classified as high-grade atypia corresponding to nuclear atypia score 3, carcinomas with apocrine differentiation tend to have a better prognosis than other triple-negative breast cancers. 2,13 In addition, although invasive pleomorphic lobular carcinoma, which often demonstrates apocrine features, has been considered more aggressive than invasive classical lobular carcinoma, there is a report that the pleomorphic variant is not significantly associated with progression-free survival or overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 At the other end of the spectrum, apocrine ductal carcinoma in situ with high nuclear grade shows marked nuclear pleomorphism and prominent nucleoli. 12 Despite that tumor cells with apocrine differentiation have large nuclei and prominent nucleoli and are classified as high-grade atypia corresponding to nuclear atypia score 3, carcinomas with apocrine differentiation tend to have a better prognosis than other triple-negative breast cancers. 2,13 In addition, although invasive pleomorphic lobular carcinoma, which often demonstrates apocrine features, has been considered more aggressive than invasive classical lobular carcinoma, there is a report that the pleomorphic variant is not significantly associated with progression-free survival or overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Apocrine ductal carcinoma in situ with low nuclear grade can sometimes be difficult to differentiate from apocrine metaplasia cytologically, but it shows complex architectural patterns such as expansive solid and papillary growth. 12 At the other end of the spectrum, apocrine ductal carcinoma in situ with high nuclear grade shows marked nuclear pleomorphism and prominent nucleoli. 12 Despite that tumor cells with apocrine differentiation have large nuclei and prominent nucleoli and are classified as high-grade atypia corresponding to nuclear atypia score 3, carcinomas with apocrine differentiation tend to have a better prognosis than other triple-negative breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] However, a concurrent invasive carcinoma focus has been found in approximately 10% of the cases. [ 19 ] Drinka et al [ 15 ] have reported concurrent invasive carcinoma in 9 (11%) cases in their study including 79 cases with a PASH diagnosis. The diagnosis was invasive ductal carcinoma in eight, and invasive micropapillary carcinoma in one of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…IHC, alongside antibodies against the most ubiquitous BM components collagen IV and laminin, is now used more frequently in routine practice for BM identification [36]. However there are some limitations as cross reactivity, propensity to stain vasculature structure [37] and the expression of some of these markers in the malignant epithelial cells [9] can complicate interpretation.…”
Section: Bm Staining Techniques and Its Pitfallsmentioning
confidence: 99%